2007
DOI: 10.1681/asn.2006080902
|View full text |Cite
|
Sign up to set email alerts
|

Early Aldosterone-Induced Gene Product Regulates the Epithelial Sodium Channel by Deubiquitylation

Abstract: The mineralocorticoid hormone aldosterone controls sodium reabsorption and BP largely by regulating the cell-surface expression and function of the epithelial sodium channel (ENaC) in target kidney tubules. Part of the stimulatory effect of aldosterone on ENaC is mediated by the induction of serum-and glucocorticoid-regulated kinase 1 (Sgk1), a kinase that interferes with the ubiquitylation of ENaC by ubiquitin-protein ligase Nedd4-2. In vivo early aldosterone-regulated mRNA now has been identified in microsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
132
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(143 citation statements)
references
References 40 publications
9
132
0
Order By: Relevance
“…We also observed that ENaC channels composed of lysine-free ␣␥ combined with wt ␤ (lanes 14 -16) were stronger expressed at the cell surface than wild-type channels or channels mutated on the lysines of all three subunits (lanes 11-13). This suggests that 1) ubiquitylation of ␣ and ␥ENaC has an impact on ENaC cell surface expression, and 2) some of the cytoplasmic lysine residues in ␤ are important for proper assembly and export of the channel to the plasma membrane consistent with our previous findings (22,24).…”
Section: Enac Gets Preferentially Cleaved In Its Non-ubiquitylatedsupporting
confidence: 88%
See 3 more Smart Citations
“…We also observed that ENaC channels composed of lysine-free ␣␥ combined with wt ␤ (lanes 14 -16) were stronger expressed at the cell surface than wild-type channels or channels mutated on the lysines of all three subunits (lanes 11-13). This suggests that 1) ubiquitylation of ␣ and ␥ENaC has an impact on ENaC cell surface expression, and 2) some of the cytoplasmic lysine residues in ␤ are important for proper assembly and export of the channel to the plasma membrane consistent with our previous findings (22,24).…”
Section: Enac Gets Preferentially Cleaved In Its Non-ubiquitylatedsupporting
confidence: 88%
“…ENaC channels containing Liddle's mutations, and hence lacking the binding sites for Nedd4-2 have been shown to be preferentially cleaved (19) and to display increased open probability Po (33), compatible with the idea that cleavage of ENaC increases Po (12). Aldosterone induces the expression of GILZ, Sgk1, and Usp2-45, which all are involved in the suppression of Nedd4-2-dependent ENaC ubiquitylation (22,34,35); accordingly they are also expected to induce ENaC cleavage, as shown for Usp2-45 in this paper. Indeed, Fejes-Toth et al (36) presented recently evidence that the proteolytic processing of ␥ENaC is reduced in mice lacking Sgk1.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…A similar problem is often encountered in preparing subcellular fractions such as brush border or basolateral membranes. Hand dissection of nephron segments has been performed for transcriptome analysis of human and rodent nephron segments 2,[19][20][21] . It often requires the perfusion and incubation of the tissue with collagenases before dissection 22,23 .…”
Section: Substructure Isolationmentioning
confidence: 99%